The rise of the cult of Rembrandt reinventing an old master in nineteenth-century France - McQueen, Alison 1969- (Amsterdam University Press, 2003)
Rembrandt's life and art had an almost mythic resonance in nineteenth-century France with artists, critics, and collectors alike using his artistic persona both as a benchmark and as justification for their own goals. This first in-depth study of the traditional critical reception of Rembrandt reveals the preoccupation with his perceived authenticity